Analysis of households? modern energy deprivations beyond connections and access in the Northwest zone of Nigeria - Aboagye, Solomon (School of Economics, 2024)
Access to modern energy is considered indispensable to the pursuit of economic growth and poverty alleviation. It also provides crucial support for the achievement of many sustainable development goals. Yet, Nigeria, the largest economy in Africa, has one of the lowest rates of net electricity generation per capita worldwide; with about 44% of its population lacking access to electricity. A remarkable 94% also lack access to any clean cooking technology despite the welldocument benefits of modern cooking solutions. The condition is worse in the Northwest zone of the country, the study area, as it hosts a substantial share of the country's population without access to electricity and modern cooking solutions. The above situation raises, at least, three research problems. Firstly, how does the current state of access to electricity impact on the profits of households' non-farm enterprise beyond connections to the national grid? Secondly, to what extent does an improvement in the attributes of modern cooking solution influence households' health outcomes against the backdrop of widespread use of biomass for cooking? Thirdly, can subsidies and credit regimes be effectively deployed to stimulate large-scale uptake of improved cookstoves? Consequently, chapter 2 evaluates the causal impact of access to electricity on the profits of households' non-farm enterprises as a latent poverty reduction pathway. Applying the generalized propensity score and inverse probability weighting of treatment methods of matching and estimation, the study found that on the basis of connections, access to electricity has limited positive causal effect on the profits of household's non-farm enterprises. However, moving beyond connections only and focusing on the attributes of electricity (i.e., the characteristics of the electricity services from the perspective of end-users which include electricity availability, reliability, affordability, quality as well as the capacity of the grid of electricity) among actual users of electricity the study established a strong positive causal impact of access to electricity on profits. Further analysis shows that in most instances, this impact however tends to be principally dependent on whether the enterprise is more profitable or otherwise. Chapter 3 assesses the attribute dimension of cooking-health nexus. Utilizing the probit and Heckman models respectively to the cough and health expenditure per capita specifications it is observed that when attributes such as exposure and safety of primary cookstove are improved, they tend to be important catalyst to reducing both cough incidence and total health expenditure per capita of the household. This important evidence could not have been learnt if the attribute dimension of the debate had not been evaluated. Ultimately, improvement in household's overall access to modern cooking solution is also associated with reduction in both cough incidence and total health expenditure per capita especially for households in higher tiers of access. Thus, a move towards clean cookstoves such as LPG/natural gas stoves, electric stoves while ensuring that households attain higher attribute tiers of modern cooking solutions could be expected to generate significant improvement in household's overall health. Chapter 4 examines the effectiveness of one-off subsidy and credit regimes in driving households' willingness to pay (WTP) for improved cookstoves (ICS). Using a heteroscedastic-corrected probit models, the results show that allowing households to pay over time coupled with a one-off subsidy of no less than 34% significantly increases the mean WTP to the extent that households are willing to pay even more than the subsidized price. Given that the regime mean WTP values are higher than the effective price of subsidized ICS, both WTP incentives are not likely to damage future pricing when ICS are eventually circulated through pure market mechanisms. Furthermore, we observe the underlying mean WTP to decline after 12 months. This suggests that a 12-month payment instalment could be the maximum effective credit duration required to drive adoption. Additionally, we observe that income, access to grid electricity, access to credit, financial inclusion are critical stimulants of WTP towards ICS.